Aiming for G7 Master Compliance through a Color Managed Digital Printing Workflow (CMDPW): Comparison of Compliance with Output Device Profile (ODP) vs. Device Link Profile (DLP) - Naik Dharavath, Haji (Journal of Graphic Engineering and Design, 2021)
The purpose of this applied research was to determine the influence of device link profile (DLP) in the color reproduction aimed at the G7 master compliance. The quality of digital color printing is determined by these influential factors: screening method applied, type of printing process, ink (dry-toner or liquid-toner), printer resolution and the substrate (paper). For this research, only the color printing attributes such as the G7 colors hue and chroma, gray balance, and overall color deviations were analyzed to examine the significant differences that exist between the two output profiles [Output Device Profile (ODP) vs Device Link Profile (DLP)]. These are the color attributes which are monitored and managed for quality accuracy during the printing. Printed colorimetry of each profile from the experiment was compared against G7 ColorSpace GRACoL 2013 (CGATS21-2-CRPC6) in CIE L* a* b* space using an IDEAlliance (Chromix/Hutch Color) Curve 4.2.4 application interface with an X-Rite spectrophotometer with an i1iO table. The measured data of each profile were run through this application (Curve 4.2.4). The data were analyzed by using the Verify Tool of the Curve 4.2.4 application to determine the pass/fail of G7 master compliance levels using G7 ColorSpace tolerances (G7 Grayscale, G7 Targeted, and G7 Colorspace). Analyzed data from the experiment revealed that the printed colorimetric values of each profile (G7 Grayscale, G7 Targeted, and G7 Colorspace) are in match (aligned) with the G7 master compliance levels (reference/ target) colorimetric values (G7 Grayscale, G7 Targeted, and G7 Colorspace). Therefore, the press run was passed by the Curve 4 application for both the profiles used/tested towards aiming for G7 master compliance. Article history: Received (February 12, 2020); Revised (October 30, 2020); Accepted (November 16, 2020); Published online (March 1, 2021)